The Relationship between Individual Factor and Risk of Low Back Pain on Broomstick Makers in Silau Padang Village, Serdang Bedagai Regency - Muhraza Siddiq; Gerry Silaban; Nurmaini (Britain International of Exact Sciences (BIoEx) Journal, 2020)
Low Back Pain (LBP) is pain in the lower back originating from the spinal area (lower back), muscles, nerves, tendons, joints and cartilage. Individual risk factor for LBP include years of service, age, gender, work attitude and smoking habits. This study aims to determine the relationship between individual factor and risk of Low Back Pain of broomstick makers in Silau Padang village, Serdang Bedagai Regency. This type of research was an observational study with cross-sectional design. The population in this study was amounted to 30 people with sampling techniques using a total sampling of 30 people. The analysis used was Chi-Square with a significance level α = 0.05, the data collection method used was a questionnaire. This study found individual factor associated with LBP risk were age (p score = 0.009, p score <0.05) and work attitude (p score = 0.01, p score <0.05). While the length of work (p score = 0.07), gender (p score = 0.1) and smoking habits (p score = 0.07) are not related to LBP risk (p score > 0.05). Only work attitudes were associated with LBP risk, so interventions were needed in the form of counseling to improve the work attitude of broomstick makers in Silau Padang Village, Serdang Bedagai Regency.